Performance for cryptography: Ahardware approach - Michail, Harris; Kakarountas, Athanasios P. (My University, 2011)
Cryptography can be considered as a special application of coding schemes. High speed execution of Encoding and Decoding processes is crucial in the majority of the so-called security schemes. In fact, the characteristics of a cryptographic algorithm in terms of throughput are usually the most important requirement to adopt the algorithm in a security scheme. As the need for higher security increases, the market urges for strong cryptographic protocols that will offer the desired degree of privacy. However, most of the algorithms now and forthcoming are complex and do not seem to be efficient for performance-oriented purposes. In this chapter, an algorithmic approach for designing high-speed cryptographic primitives is presented. Setting as target the high throughput, a complete methodology for developing various types of cryptographic primitives, focusing on hardware (without however excluding software, or a combination of them) is offered. The application of the proposed design approach also highlights the effect of designing for supercomputing on a critical application, such as cryptography. Parallelism and code transformation are few of the techniques that will be used for achieving the desired target, the implementation of the ever best proposed cryptographic primitives in terms of speed and throughput. © 2009 Nova Science Publishers, Inc. All rights reserved.
Keywords: Hash functions; Cryptographic hash